Beyond coal: When can outsider stakeholders drive transformative change? - Schifeling, Todd; Lyon, Thomas P.; Vasi, Ion Bogdan (Strategic Management Journal, 2026)
Abstract Research Summary Organizations grant stakeholders who provide valuable resources insider status in governance, excluding less valuable outsiders. Firms thereby assemble a value‐maximizing resource portfolio but face challenges when environmental shifts require adaptation that harms some insiders. We combine and extend new stakeholder and social movement theories, hypothesizing how various stakeholders influence such adaptation. Outsiders can enable adaptation depending on organizational governance and the array of insider stakeholders. For‐profit firms are less open to outsider influence, but a wider array of insiders enables outsiders to align with certain groups to overcome the opposition of others who resist change. The nature of these alignments shapes whether adaptation involves transformative divestments or exploratory investments. We test our theory in the context of the Beyond Coal movement to divest coal plants. Managerial Summary To gain access to valuable resources, organizations commit to stakeholders who provide these resources. However, this creates problems when adapting to changes in the environment that undermine the value of these resources. How can managers balance their stakeholder commitments with the need to integrate the concerns of other stakeholders demanding adaptive changes? We find that organizational governance and the configuration of stakeholder interests can create openings for adaptation. Studying a period of rapid environmental change in the US electric utility industry, for‐profit utilities were more likely to retire coal generators when activists aligned with consumer advocates, and more likely to invest in solar generators when activists aligned with prosumers.